An Exploratory Study Of Brand Equity And Malaysian Consumer Purchase Intention Towards Hotel Accommodation - Ooi, Seow Chin (2014)
Hotel accommodation are one of the important services sector that contribute to the growth of Malaysian GDP and facing challenges with the rapid changes in economic, social, political, demographic, competition, technological and others that led to consumer behavior changes. In this globalization environment, hoteliers facing stiff competition to attract more visitors for both local and foreign travelers with their limited resources. To stay sustainability, brand equity plays an important role for marketer on market positioning. Thus, Aaker’s Brand Equity Model is adopted in this study to examine the impact of brand awareness, brand loyalty, brand associations, perceived quality and brand image as independent variable to brand equity and the influence of brand equity on Malaysian consumer purchase intention towards hotel accommodations.